SUSTAINABLE DEVELOPMENT AS A COMPETITIVE ADVANTAGE IN GENERATING VALUE FOR BUSINESS ORGANIZATIONS - Bassi, Willian Di Gaetano; Gasparotto, Angelita Moutin Segoria; Gonçalves, Gilmerson Inácio (Revista Interface Tecnológica, 2020)
This article aims to analyze the industrial processes of a company that operates in the production of orange juice, as well as its operations relate to the concepts of sustainability, shared value and its harmony with development objectives (ODS). The study also addresses relevant topics for sustainable production besides presenting the motivators for changing consumer market behavior, based on the concepts of planetary boundaries and growth limits. the aggregation of value to the company and how its operations relate to these concepts, its harmony with the objectives of sustainable development (SDGs), impacts and the results generated from the sustainable development of the organization. The results show that business organizations that are sustainably responsible may gain competitive advantages considering the change in the behavior of customers and investors. It was concluded that the company studied has in its strategic planning and at its core the inclusion of sustainable actions in all operations of its value chain and this way of doing business has brought positive results to the organization and to the society where it is inserted.